Incarcerated Uterus Presenting as Short Cervix and Placenta Previa - Ali Alhousseini; Salam Zeineddine; Adham Alsamsam; Bernard Gonik; Jacques Abramowicz; Karoline Puder; Homam Saker; Edgar Hernandez-Andrade (Hindawi Limited, 2018)
Introduction. Incarcerated uterus is a rare complication of pregnancy, usually associated with retroversion. Case. A 26-year-old woman presents at 19 4/7 weeks for evaluation of a short cervix and placenta previa. On ultrasound scan, the placenta was considered previa and the cervix was not visualized. The cervix was not identified by pelvic examination and the presumptive diagnosis of short cervix was done. The patient was followed up closely and remained asymptomatic. Retrospective analysis of the ultrasound images showed a retroverted uterus with an elongated cervix compressed towards the anterior vaginal wall. At 26 weeks of gestation, ultrasound showed a cervical length of 41 mm and a fundal placenta and the diagnosis of spontaneous correction of an incarcerated uterus was made. The patient had an uncomplicated vaginal delivery at 39 3/7 weeks. Comment. Identification and close follow-up of incarcerated uterus may potentially help in avoiding serious obstetrical and surgical complications.